Surgical management of an accessory canal in a maxillary premolar: a case report - Hee-Jin Kim; Mi-Kyung Yu; Kwang-Won Lee; Kyung-San Min (Restorative Dentistry & Endodontics)
We report the surgical endodontic treatment of a maxillary first premolar with a lateral lesion that originated from an accessory canal. Although lesions originating from accessory canals frequently heal with simple conventional endodontic therapy, some lesions may need additional and different treatment. In the present case, conventional root canal retreatment led to incomplete healing with the need for further treatment (i.e., surgery). Surgical endodontic management with a fast-setting calcium silicate cement was performed on the accessory canal using a dental operating microscope. At the patient's 9-month recall visit, the lesion was resolved upon radiography.